Cathode material and device for producing ammonia by reducing nitrate under electro-catalysis
By attaching a cationic polymer layer on the outside of the catalyst during the electrocatalytic nitrate reduction process, a local alkaline environment is formed, and the problems of alkaline solution contamination and low yield in the prior art are solved, and high efficiency under neutral conditions are achieved Ammonia production.
Patent Information
- Application Number
- CN202411151416.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-01-03
AI Technical Summary
In the process of preparing ammonia with electrocatalytic nitrate reduction, a large amount of alkali is needed to add a large amount of alkaline to the cathode electrolyte, resulting in waste of resources and difficult treatment of strong alkaline wastewater, and low yield and Faraday efficiency under neutral conditions.
A cathode material including a cathode conductive matrix, a catalyst and a cationic polymer layer is designed. By attaching a cationic polymer layer to the outside of the catalyst, a local alkaline environment is formed, which promotes electrocatalytic reduction of nitrate and increases the yield of ammonia.
Under neutral conditions, the yield of ammonia and Faraday efficiency are significantly improved, the pollution of alkaline solution and the difficulty of treatment are avoided, and the catalyst and the cathode conducting matrix have strong adhesion and stable structure.
Smart Images

Figure CN119243210A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cathode material and a device for electrocatalytic nitrate reduction to produce ammonia, belonging to the field of electrochemistry. Background Art
[0002] Ammonia is one of the most important chemical products in the world. It is essential for the production of nitrogen fertilizers and various chemicals. Due to its high energy density and carbon-free characteristics, it is expected to become the next generation of hydrogen-rich fuel. At present, the industrial synthesis of NH3 is heavily dependent on the energy-intensive Haber-Bosch process, which not only requires complex facilities and harsh production conditions of high temperatures exceeding 400°C and high pressures of 100-200atm, but also relies on fossil energy production for the H2 used in the process to synthesize ammonia. Therefore, the global production of ammonia consumes a lot of energy each year, accounting for 2% of the world's total energy consumption, and causes more than 450 million tons of CO2 emissions, accounting for 1.5% of the world's total carbon emissions. Therefore, humans are in urgent need of finding a more energy-saving and low-carbon ammonia production process. The electrochemical nitrate reduction ammonia synthesis driven by renewable energy generation developed in recent years is a green and clean process for generating ammonia under ambient temperature and pressure conditions. At the same time, excessive nitrates caused by over-fertilization and industrial wastewater are discharged into surface water and underground aquifers, threatening human health. Electrochemical conversion is an effective way to solve nitrate pollution. Therefore, electrochemical reduction of nitrate to ammonia is a promising technology for both removing harmful nitrates from water and producing ammonia under ambient conditions.
[0003] At present, researchers have developed a large number of excellent catalysts for electrochemical nitrate reduction to synthesize ammonia, achieving high yields and Faraday efficiencies. It is worth noting that the pH of industrial and domestic wastewater containing harmful nitrates is close to 7, while most of the current literature on electrocatalytic nitrate reduction is carried out under strong alkaline conditions (pH ≥ 13). The yield and Faraday efficiency of nitrate reduction to synthesize ammonia under neutral conditions are generally lower than those under strong alkaline conditions. - The conversion to NH3 is a stepwise deoxygenation and hydrogenation process that relies on the active hydrogen atoms ( * To ensure the efficiency of ammonia production, it is often necessary to - A large amount of KOH / NaOH etc. is added to the electrolyte to ensure the strong alkalinity of the electrolyte, which not only causes a waste of resources, but also makes the subsequent strong alkaline wastewater treatment a problem, which is not conducive to the practical application of electrocatalytic nitrate reduction synthesis ammonia technology. Summary of the invention
[0004] In order to solve the problem that alkali needs to be added to the cathode electrolyte to meet the strong alkali requirement during the electrocatalytic reduction of nitrate to prepare ammonia, a cathode material is provided and a corresponding electrolysis device is formed. The cathode material comprises a cathode conductive substrate, a catalyst layer and a cationic polymer layer in sequence. The cathode conductive substrate can be of any shape, such as a rod or a sheet. A catalyst is attached to the outside of the rod or the sheet, and a cationic polymer is attached to the outside of the catalyst. The cationic polymer can gather hydroxide generated during the electrocatalytic reduction of nitrate near the cathode material, thereby forming a local alkaline environment at the cathode material, thereby promoting the process of electrocatalytic ammonia production and improving the ammonia production efficiency.
[0005] The scheme provided by the present invention is: a cathode material for electrocatalytic nitrate reduction to produce ammonia, comprising a cathode conductive substrate, a catalyst and a cationic polymer layer, wherein the catalyst and the cationic polymer can be mixed together and attached to the cathode conductive substrate, or can be attached to the cathode conductive substrate in a layered structure, and the preferred arrangement is to arrange the catalyst layer on the cathode conductive substrate, and then arrange the cationic polymer layer outside the catalyst layer, which is conducive to blocking the OH generated in the electrocatalytic nitrate reduction process. - The cathode conductive substrate can be in the shape of a rod or a sheet. When it is in the shape of a rod, the catalyst layer and the cationic polymer layer are sequentially arranged outward from the cathode conductive substrate as the center; when it is in the shape of a sheet, the catalyst can be attached to one side or both sides of the cathode conductive substrate, and then the cationic polymer layer is attached to the catalyst. After the electrolysis device is powered on, the nitrate ions pass through the cationic polymer layer to the catalyst, and the following reaction occurs under the catalytic action of the catalyst: NO3 - +8e - +6H2O→NH3+9OH - , the OH generated by the reaction - Under the action of the cationic polymer layer, part or all of the cationic polymers are gathered near the cathode material, forming a local strong alkaline environment near the cathode material.
[0006] The preferred catalyst is a metal nanowire array, which is generated on the cathode conductive substrate in a self-growing manner. The preferred catalyst is a cobalt metal nanowire array, which is prepared by:
[0007] S01 pre-treating the cathode conductive substrate, the conductive substrate can be any metal material, and the conductive substrate is preferably a titanium sheet; the pre-treatment process is to use acetone, ethanol, 0.1M HCl, and ultrapure water to ultrasonically clean the titanium sheet for 10 minutes respectively to clean off organic impurities and oxides on the titanium sheet;
[0008] S02 prepares a reaction solution: a cobalt salt and urea in a set ratio are dissolved in water to form a mixed reaction solution, wherein the cobalt salt is used as a cobalt source and the urea is used as a mineralizer to form a catalyst; preferably, a divalent cobalt salt, which may be Co(NO3)2.6H20 or CoSO4.7H20, and the mixed molar ratio of the divalent cobalt salt and urea is preferably 3:15. As a preferred solution preparation method, 3mmol Co(NO3)2.6H20 and 15mmol urea are dissolved in 20mL water to obtain a mixed solution;
[0009] S03: placing the mixed reaction solution in a high temperature resistant container, placing the cathode conductive substrate in the mixed reaction solution in the high temperature resistant container, and then reacting in an environment of 100-150°C, preferably at 120°C. After a certain reaction time, a pink divalent cobalt precursor, cobalt carbonate hydroxide Co2(OH)2CO3, is generated on the titanium sheet; the reaction process is:
[0010] H2NCONH2+3H2O→2NH3.H2O+CO2;
[0011] CO2+H2O→CO3 2- +2H + ;
[0012] NH3.H2O→NH4 + +OH - ;
[0013] 2Co 2+ +CO3 2- +2OH - →Co2(OH)2CO3.
[0014] The above reaction is preferably carried out in a reactor. The preferred high-temperature resistant container is a glass culture bottle. The glass culture bottle is placed in a polytetrafluoroethylene liner and then loaded into a hydrothermal reactor and placed in a 120°C oven for reaction for 6 hours.
[0015] S04 annealing to obtain the catalyst: take out the titanium sheet with the divalent cobalt precursor, flush the surface impurities with ethanol, dry it, and then anneal it at high temperature. During the annealing process, hydrogen is introduced to convert the divalent cobalt precursor into elemental cobalt. The reaction occurring in the process is as follows:
[0016] Co2(OH)2CO3+2H2→2Co+CO2+3H2O.
[0017] Preferably, hydrogen and inert gas are mixed and introduced into the reaction chamber to react with divalent cobalt. More preferably, the mixed gas is 10% H2+Ar and introduced into the reaction chamber at a flow rate of 100 sccm, which is conducive to promoting the reaction process and will not cause explosion due to the presence of hydrogen. More preferably, the reaction chamber is a tubular furnace.
[0018] Preferably, the annealing temperature is 200-500°C, preferably 400°C. If the temperature is too low, the cobalt precursor cannot be fully reduced to cobalt metal; if the temperature is too high, the reduced cobalt metal cannot maintain the nanowire morphology. The annealing time is 2h, and the heating rate is 2-10°C / min, preferably 5°C / min. If the heating rate is too high, such as exceeding 10°C / min, it may cause the catalyst precursor to fall off from the titanium sheet substrate. If the heating rate is too low, it will not have any effect on the catalyst itself, but will increase the synthesis time. 5°C / min is the preferred heating rate, and the gas flow rate is 100sccm.
[0019] Preferably, the cationic polymer is attached to the catalyst surface by chemical adsorption, physical adsorption, mechanical intercalation and charge action to form a cationic polymer layer. The cationic polymer is preferably a non-crystalline polymer, such as PDMAEMA (poly(N,N-dimethylaminoethyl methacrylate), P4VP (polytetravinylpyridine), PEI (polyethyleneimine), etc., and PEI (polyethyleneimine) is more preferred. The preparation method is:
[0020] S01 prepares an ethanol solution of a cationic polymer, preferably with a mass concentration of 1% to 10% of the cationic polymer in the solution. If the concentration is too high, the amount of PEI will be too much, the modified membrane will be too thick, and NO3 - The concentration is too low and the amount of PEI is too small to increase the local alkalinity. The optimal concentration is 3%.
[0021] S02: Evenly drop the ethanol solution of cationic polymer on the surface of the catalyst to form a cationic polymer layer after drying. The cationic polymer is attached to the catalyst surface by physical adsorption, chemical adsorption, mechanical intercalation and charge action. Taking 3% PEI as an example, the preferred amount of cationic polymer ethanol solution is: 5-20μL / cm 2 , that is, use a 3% PEI ethanol solution, take 5 to 20 μL (preferably 10 μL) of the solution and drop it on a 1 cm 2 On the catalyst electrode, at this coating amount, on the one hand, nitrate ions can smoothly pass through the cationic polymer layer to reach the catalyst surface for reaction, and on the other hand, a sufficient amount of hydroxide can be blocked around the catalyst to provide a strong alkaline environment.
[0022] It is further preferred that the thickness of the cationic polymer layer is 1 to 5 μm, as thickness above this value will hinder the formation of NO3 - Supply, below which the ability to provide local alkalinity is too weak, the thickness of the cationic polymer layer is determined by the mass fraction of the cationic polymer solution and the amount of drop coating.
[0023] The present invention uses one of the above cathode materials as a cathode to prepare an electrocatalytic nitrate reduction device to produce ammonia. The device includes a cathode chamber, an anode chamber, a cathode and an anode. The cathode chamber is filled with a cathode liquid, and the anode chamber is filled with an anode liquid. The cathode liquid and the anode liquid are separated by an anion diaphragm. The cathode liquid is a neutral electrolyte containing nitrate, wherein the concentration of nitrate is 10mM-100mM. If the concentration is too high, NO3 - If the supply is too high, the current density will not increase significantly due to the limitation that the catalyst itself does not have sufficient reactive sites. If the concentration is too low, NO3 - When the supply is insufficient, the competitive hydrogen evolution reaction will dominate. The anolyte is a neutral electrolyte without nitrate. After power is turned on, the cathode potential is -0.1 to -0.5 V relative to the reversible hydrogen electrode.
[0024] The beneficial effects of the present invention include: the electrocatalytic nitrate reduction ammonia production device of the present invention generates OH by reducing nitrate - The characteristics of the method are used to increase the ammonia production in the neutral nitrate reduction system. It does not need to rely on alkaline solution to provide an alkaline reduction environment, which solves the problem of high pollution and high difficulty in handling of alkaline solution in the ammonia production process.
[0025] The device of the present invention utilizes the hydroxide generated during the reduction of nitrate, and combines the layered design of the cathode material to localize the hydroxide around the catalyst, promoting the water splitting and generating * H, satisfies NO3 - When the reduction reaction occurs * The need for H increased the ammonia yield to 0.82 mmol cm -2 h -1 (at -0.5V vs. RHE, no iR correction);
[0026] The device of the present invention grows the catalyst in situ on the cathode conductive substrate, so that the catalyst has strong adhesion to the cathode conductive substrate, the structure is stable, and the specific surface area is large, which provides more possibilities for the nitrate ion to react with the catalyst on the conductive substrate;
[0027] The present invention provides a cationic polymer layer on the outer layer, which, on the one hand, does not hinder the movement of nitrate to the cathode and accelerates the reaction process, and on the other hand, can localize the hydroxide generated by the reaction at the catalyst;
[0028] The present invention uses a cobalt metal nanowire array as a catalyst and PEI as a cationic polymer, so that the cationic polymer is attached to the catalyst surface through bonding, the structure is stable, and the influence of the cationic polymer and other impurities in the electrolyte on the nitrate reduction reaction is reduced;
[0029] The device of the present invention can effectively improve the ammonia production efficiency within a wider range of electrolysis potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Cross-sectional view of cathode material after modification of catalyst with cationic polymer;
[0031] Figure 2 Electrolysis device structure diagram;
[0032] Figure 3 Schematic diagram of the working principle of the cationic polymer layer;
[0033] Figure 4-Figure 9 A histogram of ammonia production rates of various embodiments and comparative examples at different cathode potentials;
[0034] In the figure, 1 is an electrochemical workstation, 2 is a cathode liquid, 3 is a cationic polymer layer, 4 is a cathode catalyst, 5 is an anion exchange membrane, 6 is an anode, and 7 is an anode liquid. DETAILED DESCRIPTION
[0035] The present invention is further explained in detail below by way of specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0036] Example 1
[0037] Preparation of cathode materials
[0038] 1. Cut a titanium sheet with a thickness of 0.03 mm into a rectangular sheet of 1.5 cm × 5.0 cm, and ultrasonically clean it with acetone, ethanol, 0.1 M HCl, and ultrapure water for 10 min respectively to remove organic impurities and oxides on the titanium sheet;
[0039] 2. Take 3mmol Co(NO3)2.6H20 and 15mmol urea, dissolve in 20mL water, stir magnetically until completely dissolved and evenly dispersed, pour into a 20mL glass culture bottle, place the cleaned titanium sheet in the culture bottle, place the titanium sheet at an angle, and cover the titanium sheet with the solution. Place the open culture bottle in a 50mL polytetrafluoroethylene liner, then put it in a 50mL hydrothermal reactor, place it in a 120℃ oven to react for 6h, and generate a pink divalent cobalt precursor cobalt carbonate hydroxide Co2(OH)2CO3 on the titanium sheet. The reaction process is as follows:
[0040] H2NCONH2+3H2O→2NH3.H2O+CO2;
[0041] CO2+H2O→CO3 2- +2H + ;
[0042] NH3.H2O→NH4 + +OH - ;
[0043] 2Co 2+ +CO3 2- +2OH - →Co2(OH)2CO3;
[0044] 3. After the reactor is cooled to room temperature, the titanium sheet is taken out, the surface impurities are washed off with ethanol, and the sheet is dried in a vacuum blast drying oven at 60°C for about 1 hour until it is completely dry. Then, it is annealed at 400°C for 2 hours in an atmosphere of 10% H2+Ar, and the divalent cobalt precursor is reduced in a hydrogen atmosphere to generate cobalt element. The heating rate is 5°C / min, and the gas flow rate is 100sccm. After the sheet is naturally cooled to room temperature, it is taken out to obtain the desired catalyst. The reaction process is as follows: Co2(OH)2CO3+2H2→2Co+CO2+3H2O;
[0045] 4. Modification of the catalyst by cationic polymer PEI:
[0046] A weighed 30 mg of PEI powder, dissolved in 0.97 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 3% PEI ethanol solution;
[0047] B. Cut the titanium sheet loaded with catalyst into 1cm×1cm size, use a pipette to absorb 10μL PEI ethanol solution, evenly drip it on the catalyst surface, and place it in a fume hood for 12h to allow the ethanol to completely evaporate. PEI adheres to the catalyst surface through physical and chemical adsorption with the catalyst to form a uniform film, completing the modification of the catalyst. After modification, the cross section is observed using a scanning electron microscope, as shown in Figure 1 It can be seen that the thickness of the cobalt metal nanowire array catalyst is about 3 μm, and the thickness of the formed PEI layer is also about 3 μm, and the two are in close contact.
[0048] 5. Build an electrolysis device
[0049] The structure diagram of the electrolysis device is as follows: Figure 2 As shown, it is an H-type electrolytic cell, including a cathode chamber and an anode chamber, 40mL 0.5M K2SO4+0.1M KNO3 is placed in the cathode chamber, 40mL 0.5M K2SO4 is placed in the anode chamber, the cathode material prepared as above is used as the cathode, the graphite rod is used as the anode, the saturated Ag / AgCl electrode working under neutral conditions is used as the reference electrode, and the FAA-130 anion exchange membrane is used as the diaphragm between the cathode chamber and the anode chamber. The cathode chamber needs to maintain good airtightness and is provided with an air inlet and an air outlet.
[0050] Before applying the potential, high-purity argon gas was passed into the cathode liquid at a flow rate of 100 sccm for 10 min to remove dissolved oxygen in the cathode liquid. All initial cathode potentials were converted to the potential conversion equation, E RHE=E Ag / AgCl +0.059*pH+0.197 (0.197 is the standard potential of a saturated Ag / AgCl electrode), which is converted to the potential relative to the reference electrode used. During the electrolysis process, the cathode liquid is magnetically stirred at 400 rpm to ensure that NO3 - The system was supplied with high-purity argon gas (flow rate of 20 sccm) to eliminate the influence of oxygen reduction reaction (ORR).
[0051] After the electrolytic cell is powered on, oxygen evolution reaction occurs at the anode: 2H2O→4H + +O2+4e - , nitrate reduction reaction occurs at the cathode: NO3 - +8e - +6H2O→NH3+9OH - .
[0052] In this embodiment, the catalyst surface is modified by using cationic polymer to form a thin film on the catalyst surface. The cationic polymer can slow down the OH - Diffusion allows the OH generated on the catalyst surface to - can be mostly bound to the catalyst surface, such as Figure 3 , so that the pH on the catalyst surface is much higher than the pH of the bulk electrolyte, achieving the effect of improving ammonia yield.
[0053] Example 2
[0054] The difference from Example 1 is that the cathode liquid is 40 ml of 1M KOH+0.1M KNO3 solution with pH=14.
[0055] Comparative Example 1
[0056] The difference from Example 1 is that the catalyst is not modified, that is, the cathode catalyst is not treated with the cationic polymer PEI.
[0057] Comparative Example 2
[0058] The difference from Example 1 is that (1) the catalyst is not modified, that is, the cathode catalyst is not treated with the cationic polymer PEI; and (2) the cathode liquid is 40 ml of 1M KOH+0.1M KNO3 solution with a pH of 14.
[0059] Example 3
[0060] The only difference from Example 1 is that the catalyst is modified by using PDMAEMA. The modification method is as follows: A. Weigh 30 mg of PDMAEMA powder, dissolve it in 0.97 g of ethanol, and disperse it by ultrasonic until it is completely uniform, to obtain a PDMAEMA ethanol solution with a mass fraction of 3%;
[0061] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 10 μL of PDMAEMA ethanol solution, evenly drop it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PDMAEMA adheres to the catalyst surface through physical and chemical adsorption with the catalyst to form a uniform film, thereby completing the modification of the catalyst.
[0062] Example 4
[0063] The only difference from Example 1 is that the catalyst is modified by using P4VP. The modification method is as follows: A. Weigh 30 mg of P4VP powder, dissolve it in 0.97 g of ethanol, and disperse it by ultrasonic until it is completely uniform, to obtain a P4VP ethanol solution with a mass fraction of 3%;
[0064] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 10 μL of P4VP ethanol solution, evenly drip it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. P4VP adheres to the catalyst surface through physical and chemical adsorption with the catalyst to form a uniform film, completing the modification of the catalyst.
[0065] Example 5
[0066] The only difference from Example 1 is that the catalyst is modified using a 1% PEI ethanol solution. The modification method is:
[0067] A weighed 10 mg of PEI powder, dissolved in 0.99 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 1% PEI ethanol solution;
[0068] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 10 μL of PEI ethanol solution, evenly drip it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PEI adheres to the surface of the catalyst through physical and chemical adsorption with the catalyst to form a uniform film, thus completing the modification of the catalyst.
[0069] Example 6
[0070] The difference from Example 1 is that the catalyst is modified using a 5% by mass PEI ethanol solution, and the modification method is:
[0071] A weighed 50 mg of PEI powder, dissolved in 0.95 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 5% PEI ethanol solution;
[0072] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 10 μL of PEI ethanol solution, evenly drip it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PEI adheres to the surface of the catalyst through physical and chemical adsorption with the catalyst to form a uniform film, thus completing the modification of the catalyst.
[0073] Example 7
[0074] The difference from Example 1 is that the catalyst is modified using a 10% by mass PEI ethanol solution, and the modification method is:
[0075] A weighed 100 mg of PEI powder, dissolved in 0.9 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 10% PEI ethanol solution;
[0076] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 10 μL of PEI ethanol solution, evenly drip it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PEI adheres to the surface of the catalyst through physical and chemical adsorption with the catalyst to form a uniform film, thus completing the modification of the catalyst.
[0077] Example 8
[0078] The difference from Example 1 is that the amount of cationic polymer solution dripped on the catalyst is 5 μL / cm 2 , that is, the modification method is:
[0079] A weighed 30 mg of PEI powder, dissolved in 0.97 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 3% PEI ethanol solution;
[0080] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 5 μL of PEI ethanol solution, and evenly apply it on the surface of the catalyst. Place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PEI adheres to the surface of the catalyst through physical and chemical adsorption with the catalyst to form a uniform film, completing the modification of the catalyst.
[0081] Example 9
[0082] The difference from Example 1 is that the amount of cationic polymer solution dripped on the catalyst is 15 μL / cm 2 , that is, the modification method is:
[0083] A weighed 30 mg of PEI powder, dissolved in 0.97 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 3% PEI ethanol solution;
[0084] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 15 μL of PEI ethanol solution, evenly drip it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PEI adheres to the surface of the catalyst through physical and chemical adsorption with the catalyst to form a uniform film, thus completing the modification of the catalyst.
[0085] Example 10
[0086] The difference from Example 1 is that the amount of cationic polymer solution dripped on the catalyst is 20 μL / cm 2 , that is, the modification method is:
[0087] A weighed 30 mg of PEI powder, dissolved in 0.97 g of ethanol, and ultrasonically dispersed until completely uniform to obtain a 3% PEI ethanol solution;
[0088] B. Cut the titanium sheet loaded with the catalyst into a size of 1 cm × 1 cm, use a pipette to absorb 20 μL of PEI ethanol solution, evenly drip it on the surface of the catalyst, and place it in a fume hood for 12 hours to allow the ethanol to completely evaporate. PEI adheres to the surface of the catalyst through physical and chemical adsorption with the catalyst to form a uniform film, completing the modification of the catalyst.
[0089] After the electrolysis is completed, the ammonia production of the cathode liquid in each embodiment and comparative example is detected by salicylic acid spectrophotometry. The specific operation is as follows: the electrolyte in the cathode chamber is collected, ultrasonically dispersed, the total charge of the reaction is calculated by it curve integration, the maximum ammonia production (calculated with Faraday efficiency of 100%) is estimated, and a small amount of sample is added with ultrapure water of different volume ratios to dilute the sample by a certain multiple so that the concentration of the ammonia to be measured is within the range of the standard curve, and the absorbance of the generated indophenol blue compound is less than 1. Take 2mL of the diluted electrolyte, add 2mL of 1M NaOH solution containing 5wt% sodium citrate and salicylic acid, 1mL of 0.05M NaClO solution, and 0.2mL of 1ωt% sodium nitroprusside solution in sequence, mix well, react in a dark environment for 2h, measure its absorbance at 697nm with an ultraviolet visible spectrophotometer, and calculate the ammonia production according to the standard curve.
[0090] The devices in the embodiments and comparative examples were electrolyzed at cathode potentials of -0.1 V vs. RHE, -0.2 V vs. RHE, -0.3 V vs. RHE, -0.4 V vs. RHE, and -0.5 V vs. RHE for 20 min (without iR compensation). After the electrolysis, the ammonia production rate was tested. The test results are shown in FIG. Figure 4-9It can be seen that the devices in Examples 1 and 2 show high ammonia production rates in both alkaline cathode liquid and neutral cathode liquid, and the original alkalinity strength of the cathode liquid has no significant effect on the ammonia production rate when the modified catalyst is used (modification can allow the catalyst to have the same high performance in neutral as in alkaline solution); the unmodified catalysts in Comparative Examples 1 and 2 can have a higher ammonia production rate in alkaline cathode liquid, but the ammonia production rate in neutral cathode liquid is much lower than that in alkaline cathode liquid, and the electrocatalytic nitrate reduction ammonia production is highly dependent on the alkaline environment of the solution. By comparing Examples 1, 3, 4 and Comparative Example 1, it can be seen that the ammonia production rates of the catalysts treated with cationic polymers PEI, PDMAEMA, and P4VP are all higher than those of the untreated catalysts to varying degrees, indicating that the cationic polymer layer is beneficial to improving the ammonia production rate. By comparing Examples 1, 5, 6, 7 and Comparative Example 1, it can be seen that cationic polymer solutions of different mass fractions can all improve the ammonia production rate to varying degrees, and the mass fraction of the cationic polymer solution used has different effects on the ammonia production rate by nitrate reduction; by comparing Examples 1, 8, 9, 10 and Comparative Example 1, it can be seen that the amount of polymer cationic solution used for drip-coating modification of the catalyst has different effects on the ammonia production rate by nitrate reduction.
[0091] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A device for producing ammonia by electrocatalytic nitrate reduction, characterized in that: It includes a cathode chamber, an anode chamber, a cathode and an anode, wherein a cathode liquid is placed in the cathode chamber, an anode liquid is placed in the anode chamber, ions are exchanged between the cathode liquid and the anode liquid via an ion diaphragm, and the cathode liquid contains nitrate ions; The cathode includes a cathode conductive matrix, a catalyst and a cationic polymer. Under the action of the catalyst, the nitrate ions are reduced at the cathode to produce ammonia and OH. - Under the action of the cationic polymer, the OH - Part or all of them gather around the catalyst to provide an alkaline environment for the nitrate reduction reaction.
2. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 1, characterized in that: The reduction reaction occurring at the cathode is: NO3 - +8e - +6H2O→NH3+9OH - ; The cathode has one of the following structures: The cathode comprises a three-layer structure, which is a cathode conductive substrate, a catalyst layer and a cationic polymer layer in sequence, wherein the catalyst layer is attached to one side of the cathode conductive substrate, the cationic polymer layer is attached to the catalyst layer side, and the cathode conductive substrate is a sheet; The cathode includes a five-layer structure, which is a cationic polymer layer, a catalyst layer, a cathode conductive substrate, a catalyst layer and a cationic polymer layer in sequence. Catalyst layers are arranged on both sides of the cathode conductive substrate, and a cationic polymer layer is arranged outside the catalyst layer. The cathode conductive substrate is a sheet. The cathode is composed of a cathode conductive matrix, a catalyst layer and a cationic polymer layer from the center to the outside, and the cathode conductive matrix is a columnar structure.
3. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 1, characterized in that: The catalyst is grown on the cathode conductive substrate in the form of a metal nanowire array, preferably a cobalt metal nanowire array, and the preparation method of the cobalt metal nanowire array is: S01 pre-treating the cathode conductive substrate to remove impurities on the surface of the cathode conductive substrate; S02 placing the cathode conductive substrate in a mixed solution of cobalt salt and urea and reacting at 100-150° C. to generate a divalent cobalt precursor Co2(OH)2CO3 on the surface of the cathode conductive substrate; S03: placing the cathode conductive substrate in a reducing atmosphere for annealing to generate a cobalt metal nanowire array on the cathode conductive substrate.
4. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 3, characterized in that: The cobalt salt is cobalt nitrate or cobalt sulfate, and the molar ratio of the cobalt salt to urea is 1:(5-10); the annealing temperature is 200°C to 500°C, and the reducing atmosphere is a mixed gas of H2 and Ar, wherein the volume proportion of H2 in the mixed gas is 10%-100%.
5. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 1, characterized in that: The preparation method of the cationic polymer layer is as follows: S01 prepares a cationic polymer solution; S02: coating the solution on a cathode conductive substrate loaded with an electrocatalytic nitrate reduction catalyst, and forming a cationic polymer layer on the catalyst surface through bonding.
6. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 5, characterized in that: The thickness of the polycation layer is 1-5 μm, preferably 3 μm.
7. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 1, characterized in that: The solute in the cationic polymer solution is a non-crystalline polymer, preferably a combination of one or more of PDMAEMA, P4VP and PEI.
8. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 1, characterized in that: The solute in the solution is PEI, the solvent is ethanol, the mass fraction of PEI in the solution is 1% to 10%, and the coating amount of the solution on the catalyst surface is 5 to 20 μL cm -2 .
9. The device for electrocatalytic nitrate reduction to produce ammonia according to claim 1, characterized in that: The cathode chamber satisfies one or more of the following combinations: — NO3 in cathode liquid - Concentration is 10mM-100mM; - the cathode liquid is a neutral electrolyte with a pH of 6-8. In this case, preferably, the ion membrane is an anion membrane, the cathode liquid is a mixture of K2SO4 and KNO3, and the anode liquid is K2SO4; - cathode potential is -0.1 to -0.5 V relative to the reversible hydrogen electrode; - The cathode catalyst is one or more of Cu-based, Fe-based, Co-based, and Ni-based, and the cathode conductive substrate is a metal conductive substrate.
10. An electrocatalytic nitrate reduction cathode material, characterized in that: The invention comprises a conductive substrate, on which a metal nanowire array is grown, the metal nanowire array is a catalyst for electrocatalytic nitrate reduction, and a cationic polymer layer is arranged on the metal nanowire array. The preparation method of the cationic polymer layer is as follows: S01 prepares a cationic polymer solution; S02: coating the cationic polymer solution on the cathode conductive substrate loaded with the catalyst, and forming a cationic polymer layer on the catalyst surface through bonding.
